Complete Genome Sequence of Streptococcus pyogenes M/emm44 Strain STAB901, Isolated in a Clonal Outbreak in French Brittany - Soriano, Nicolas (Genome Announc, 2014)
We report the complete genome sequence of an invasive isolate of Streptococcus pyogenes M/emm44, belonging to a clonal outbreak that occurred in French Brittany. The genome is composed of 1,795,608 bp, with a GC content of 38.5%, has 1,358 identified coding sequences (CDSs), and harbors a novel Tn916-like transposon (Tn6253).